HUBUNGAN POLA ASUH ORANG TUA TERHADAP KARAKTER DISIPLIN SISWA KELAS V DI SDN 007 PULAU BIRANDANG - Renatah Ayuni; Hendri Marhadi; Erlisnawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the relationship between parenting style and students' disciplinary character in the fifth grade of SDN 007 Pulau Birandang. The research used a quantitative correlational method with a total sampling technique involving 29 students. Data were collected using questionnaires, observation, and documentation. The research instrument was tested for validity and reliability, and the results indicated that all items were valid and reliable. The data were analyzed using simple regression. The results showed that there was a positive and significant relationship between parenting style and students’ disciplinary character, with a t-value of 3.741 greater than the t-table value of 1.699, and a significance value of 0.001 < 0.05. The study concludes that better parenting style contributes to improved student discipline. Democratic parenting style was found to be the most influential in forming student discipline in SDN 007 Pulau Birandang.